Effect of the soil water characteristic curve on the stability of partially saturated slopes - Shanka, Akshaya (My University, 2024)
Rainfall significantly contributes to slope failure in unsaturated slopes by causing a reduction in matrix suction and subsequent decline in shear strength of the soil. Understanding the relationship between matrix suction and moisture content is crucial for describing the hydraulic behavior of unsaturated soil, typically represented by the Soil-Water Characteristic Curve (SWCC). This study focuses on assessing how SWCC affects the stability of partially saturated soil during infiltration us ing fully coupled-flow deformation analysis in PLAXIS 2D. To enhance efficiency and automate analyses for numerous iterations, PLAXIS-remote scripting is utilized.Parameters that quantify the SWCC are utilized to depict the properties of unsaturated soils. The Van- Genuchten parameters, which describe the hydraulic behavior of unsaturated soil, have been determined based on the SWCC. Furthermore, the impact of Van Genuchten parameters (ga , gn) that best fit the SWCC on the stability of unsaturated soil under rainfall conditions has been studied. The slope stability under infiltration is initially examined based on the derived VG parameters. Subsequently, the impact of VG parameters on the stability of unsaturated slopes is assessed by determining five different values for each parameter:ga and gn. These values are utilized to generate five unique sets of VG parameters, resulting in 25 combinations. The stability of the unsaturated slope under the effect of rainfall is then evaluated for these 25 combinations of VG parameters. In addition to hydraulic parameters, factors such as the geometry of the slope and the shear strength properties of the soil also play a significant role in influencing the stability of unsaturated slopes. Therefore, a sensitivity analysis is conducted by varying the slope geometry and shear strength properties to explore the impact of 25 different combinations of Van Genuchten parameters. The resulting values of FOS are then compared with the original slope geometry and shear strength properties for all 25 combinations of Van Genuchten parameters under the effect of rainfall, in order to investigate the slope stability.Upon increasing the values of ga and gn, the FOS of the slope significantly decreases under the influence of rainfall. Moreover, sensitivity analysis results indicate that the stability of an unsaturated slope under consistent rainfall infiltration is directly correlated with the VG parameters and shear strength parameters, while being inversely proportional to the slope’s geometry.
Keywords: Unsaturated Slope; SWCC; matrix suction; fully coupled flow-deformation analysis; FOS; PLAXIS 2D; remote scripting; python codes